Romanceiro da Inconfidência: o passado que não deu uma epopeia - PELET, Lúcia de Fátima (2012)
This study proposes to analyze the epic components existing in the Romanceiro da Inconfidência, taken by the poet Cecília Meireles as reasons to relieve the Inconfidência Mineira episode, occurred in the eighteenth century. The principal objective is shown the transformation of these reasons on essentially lyrical elements, since this long poem is seen by some segments of literary criticism as an epic and separated from the intimate style caecilian. Based on Iliad, the first chapter discusses the limits of literary genres, addressing three factors: past history, the configuration of the heroic characters (especially Tiradentes) and the heterogeneity-plurality of voices. The theoretical framework has the postulates of Hegel and Staiger, Benjamin, Lukács and Bakhtin. The second chapter aims to show the cohesion between the Romanceiro da Inconfidência and the lyrical poetry caecilian generally. For it focuses on three resources: the intimacy, time and poetic images, through of theories of Collot, Saint Augustine, Paul Ricoeur, Jorge Luis Borges, Alfredo Bosi and Bachelard.